Battle Angel Alita. Deluxe edition, Vol. 1, Treasure amid the trash [Graphic Novel] - Kishiro, Yukito (Battle Angel Alita., 2017)
After more than a decade out of print, the original cyberpunk action classic returns in glorious 400-page hardcover deluxe editions, featuring an all-new translation, color pages, and new cover designs!